2001
DOI: 10.1046/j.1523-1755.2001.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluvastatin on acute renal allograft rejection: A randomized multicenter trial

Abstract: Contrary to the reported effects of statins, fluvastatin had no effect on the incidence or severity of acute rejection following renal transplantation. There were no increases in adverse events. A significant and potentially beneficial alteration in the lipid profile was observed in the early post transplant period. We conclude that fluvastatin may be used safely to correct dyslipidemia in patients with end-stage renal failure through the peri-transplant period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 27 publications
0
54
0
3
Order By: Relevance
“…Individuals receiving fluvastatin had a reduction in LDL cholesterol level by 18%, total cholesterol (TC) by 10% and an augmented increase in the HDL cholesterol by 6%. There was no increase in adverse events from the use of statin and no reduction in the acute rejection rates in RTR [60] . A recent metaanalysis of statin use in RTR included 22 studies and found the inconclusive effects of statin on all-cause mortality and kidney function.…”
Section: Kidney Transplant Patientsmentioning
confidence: 85%
“…Individuals receiving fluvastatin had a reduction in LDL cholesterol level by 18%, total cholesterol (TC) by 10% and an augmented increase in the HDL cholesterol by 6%. There was no increase in adverse events from the use of statin and no reduction in the acute rejection rates in RTR [60] . A recent metaanalysis of statin use in RTR included 22 studies and found the inconclusive effects of statin on all-cause mortality and kidney function.…”
Section: Kidney Transplant Patientsmentioning
confidence: 85%
“…195,227,[231][232][233][234][235][236][237][238][239][240][241][242][243]245 The ALERT trial captured the largest sample for the longest follow-up (Ͼ10 000 patientyears) and found no difference in the frequencies of total or types of adverse events among patients treated with fluvastatin compared with placebo, including no differences in infections, malignancies, substantial creatinine kinase elevations, or rhabdomyolysis. 227 Importantly, these studies do not suggest harm attributable to statin therapy started before or perioperatively in patients undergoing kidney transplantation.…”
Section: Postoperative Medical Management Of Cardiovascular Risk Aftementioning
confidence: 99%
“…Two small initial randomized controlled trials (RCTs) investigating statins for prevention of allograft kidney rejection showed significantly lower rejection rates in statin-treated patients (140,141). However, 3 subsequent RCTs demonstrated no significant differences between short-term rejection rates between 400 ABELES AND PILLINGER patients in the intervention and control arms (142)(143)(144). It is unclear whether these studies failed to replicate the earlier findings because of drug inefficacy or because of drug choice and dosage.…”
Section: Statin Trials In Human Inflammatory and Autoimmune Diseasesmentioning
confidence: 99%